2009
DOI: 10.1158/1541-7786.mcr-08-0522
|View full text |Cite
|
Sign up to set email alerts
|

Exon Array Profiling Detects EML4-ALK Fusion in Breast, Colorectal, and Non–Small Cell Lung Cancers

Abstract: The echinoderm microtubule-associated protein-like 4-anaplastic lymphoma kinase (EML4-ALK) fusion gene has been identified as an oncogene in a subset of non-small cell lung cancers (NSCLC). We used profiling of cancer genomes on an exon array to develop a novel computational method for the global search of gene rearrangements. This approach led to the detection of EML4-ALK fusion in breast and colorectal carcinomas in addition to NSCLC. Screening of a large collection of patient tumor samples showed the presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
191
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(203 citation statements)
references
References 34 publications
11
191
0
1
Order By: Relevance
“…In some instances (FGFR2, ALK or NTRK1), overexpression of the TK gene was associated with amplification or translocation of the corresponding locus. The same genetic alterations have been previously reported in CRC cells and patients [26][27][28] , thus validating our approach. Our data further suggest that overexpression of TK sustains primary resistance to EGFR blockade, and could be used to identify patients unlikely to respond to cetuximab or panitumumab.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In some instances (FGFR2, ALK or NTRK1), overexpression of the TK gene was associated with amplification or translocation of the corresponding locus. The same genetic alterations have been previously reported in CRC cells and patients [26][27][28] , thus validating our approach. Our data further suggest that overexpression of TK sustains primary resistance to EGFR blockade, and could be used to identify patients unlikely to respond to cetuximab or panitumumab.…”
Section: Discussionsupporting
confidence: 86%
“…We decided to focus on TKs for which targeted agents are in clinical trial or are already approved for treatment, namely ALK, FGFR2, KIT, NTRK1, NTRK2, RET and PDGFRA. This analysis revealed that the overexpression of NTRK1 and FGFR2 is associated to molecular alterations, such as gene translocation (NTRK1) or gene amplification (FGFR2; Supplementary Figs 5 and 6), previously described in cellular models and in cancer patients [26][27][28] , thus validating the experimental approach. The other TK outlier genes were not previously reported in CRC cells.…”
Section: Resultssupporting
confidence: 70%
“…3), and at low frequency in other types of tumor, such as rhabdomyosarcoma (RMS; ref. 4), extramedullary plasmacytoma (5), renal cell carcinoma (6), thyroid cancer (7), basal cell carcinoma (8), breast cancer, and colorectal cancer (9,10). Moreover, aberrant activation or overexpression of full-length ALK has an oncogenic role in neuroblastoma (11,12) and glioblastoma multiforme (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…2 Recurrent rearrangements of ALK have since been described with numerous partner genes in anaplastic lymphoma and other hematolymphoid malignancies as well as in solid tumors such as inflammatory myofibroblastic tumors, esophageal squamous cell carcinoma, breast carcinoma, colonic adenocarcinoma, lung adenocarcinoma and, recently, pediatric renal cell carcinoma (RCC). [3][4][5][6][7][8][9] The ALK protein is a membrane-associated tyrosine kinase belonging to the insulin receptor superfamily. Outside of the embryonic state, ALK expression is normally confined to the central nervous system.…”
mentioning
confidence: 99%